Uprzednie porozumienie cenowe pomiędzy podmiotem powiązanym i administracją podatkową - rozwiązania stosowane w krajach Unii Europejskiej a projektowane zmiany ordynacji podatkowej - Skwierczyński, Stanisław (Advance Pricing Agreements between Related Entity and Tax Administration - the Solutions Applied in the European Union vs. Intended Changes in Polish Tax Ordination, 2005)
Polish tax administration prepares to implement Advance Pricing Agreements Institution, which is to replace currently used administrative and judicial mechanisms that deal with transfer price assessment in transactions between related entities. The subject of the publication is to discuss the solutions designed in Poland in relation to the legal standards that are in force in the European Union, in particular the Advance Pricing Agreements as well as the procedure and the legal implications resulting from its implementation. The author discusses the advantages and disadvantages of Advance Pricing Agreements Institution from the taxpayer's and tax organs' viewpoint and expresses an opinion that this institution should contribute to restrictive use of transfer prices between related entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 97-107